2015
DOI: 10.1016/j.bbmt.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Allogeneic Hematopoietic Cell Transplantation for Children with FMS-Like Tyrosine Kinase 3 Internal Tandem Duplication–Positive Acute Myelogenous Leukemia

Abstract: FMS-like tyrosine kinase 3 (FLT3) internal tandem duplication (ITD) is a somatic mutation associated with poor outcome when treated with chemotherapy alone. In children, hematopoietic stem cell transplantation (HSCT) is recommended, but very limited data on outcome are reported. We determined the outcome of 29 children with FLT3/ITD-positive acute myelogenous leukemia (AML) who underwent allogeneic HSCT in 4 pediatric centers. Eleven patients (38%) received matched related donor hematopoietic stem cells and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Data from COG as well as a number of adult trials have shown the benefit of HCT in first CR for this group of patients. (13, 15),(19, 2628) For patients in the No-GO cohort, there were no differences in outcome measures according to HCT vs. no-HCT status, suggesting that GO may enhance the beneficial impact of HCT in reducing relapse risk. Our findings suggest that indeed the most optimal outcome for this high-risk cohort may be achieved with the use of induction GO followed by HCT in first CR.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data from COG as well as a number of adult trials have shown the benefit of HCT in first CR for this group of patients. (13, 15),(19, 2628) For patients in the No-GO cohort, there were no differences in outcome measures according to HCT vs. no-HCT status, suggesting that GO may enhance the beneficial impact of HCT in reducing relapse risk. Our findings suggest that indeed the most optimal outcome for this high-risk cohort may be achieved with the use of induction GO followed by HCT in first CR.…”
Section: Discussionmentioning
confidence: 94%
“…(1318) Although allogeneic hematopoietic stem cell transplant (HCT) increases the survival to approximately 65% for this cohort, alternative therapeutic approaches are needed to improve long-term survival in a significant number of children with this lesion. (13, 19) Because the limits to which conventional treatment can be intensified have been reached, the use of alternative approaches such as immunotherapy are necessary to further improve outcomes. In this study, we investigated the impact of CD33 targeting with GO in FLT3 /ITD patients as a method to improve outcomes for this high-risk group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The use of TBI has been associated with a superior disease-free survival in very high-risk AML patients with the somatic mutation FMS-like tyrosine kinase 3 internal tandem duplication. 16 In ALL patients, TBI is widely used as it has not been shown that TBI could be replaced by chemotherapy. [17][18][19] Since the late 1970s, both TBI therapy and supportive care have greatly improved, and this may result in less frequent late effects among the more recently treated survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there exists much data supporting allo-SCT in FLT3-positive patients, in this context, it is still necessary to define risk subcategories (with different transplantation efficacy) based on FLT3-related (such as the FLT3 allelic burden) and FLT3-unrelated parameters (such as the presence of other pretransplantation predictive factors) [8,[10][11][12][13][14][15][16].…”
mentioning
confidence: 99%